DIGITAL MEDIA AND MEDIA LEGISLATION OF THE REPUBLIC OF SERBIA - Vučković, Jelena (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The modern age is redefining human communication and raising the question of whether online visitors can cope with so much freedom, which also applies to various media platforms. Thus, the Internet as a global medium opens new legal issues and poses new challenges in the field of media legislation. Information policy and legislation must adequately respond to the challenges of the new digital age. Virtual media space becomes a substitute for real space. The issue of ownership over the (private or public) media has become a secondary issue because, in both cases, the media cater for the interests of specific social elites which extend beyond the normative framework of objectivity and freedom. New media are a new challenge for law and values, not only in a speculative sense but also in a real, procedural and human sense. In times of Information and Communication Technologies (ICT), law should not turn a blind eye to the developments in the virtual space. The question is whether the legislation should be the same for all media (traditional and new ones). It is certainly the goal of media legislation, but also a huge challenge. The first step in addressing this issue should be the provision of a broad and realistic definition of the concept of media, which will ensure the recognition of the new media. Secondly, media regulations and principles which refer to the new media should be more flexible and less strict as compared to the traditional media (but only provisionally); it is more purposeful than turning a blind eye to the new media. Non-recognition and non-regulation of information dissemination via the Internet opens the possibility of causing much greater damage to the public interest.
Keywords: media; concept of media; new media legislation; media freedom